Urbanization and habitat loss: an overview of rapidly growing cities in Saudi Arabia - Bedur Faleh A. Albalawi (Frontiers in Sustainable Cities)
The rapid spread of urban areas operates as a main element in habitat loss patterns in rapidly expanding cities of the Global South. The review critically examines the natural environmental challenges associated with urban expansion, with particular emphasis on their impact on habitat degradation, biodiversity loss, and weather pattern alterations. This work aims to investigate biodiversity changes in habitat structure resulting from rapid urbanization, with a primary focus on Saudi cities, supported by comparative examples from other rapidly urbanizing cities in the Global South. Urbanization in Saudi Arabia; as an example; serves as an analysis that demonstrates swift population growth’s effect on desert ecosystems combined with coastal environments along with wetland habitats. The adverse impacts of urbanization can be mitigated through sustainable planning approaches that incorporate green infrastructure and targeted conservation strategies. The Saudi green initiative presents an example of how development can work harmoniously with ecological conservation through organized sustainable approaches. Urban planning requires integration of biodiversity elements and strict environmental regulations to reduce adverse effects of urban development so cities can maintain sustainability standards.